The Influence of Brand Image, Advertising Appeal, and Lifestyle on The Purchase Intention of Janji Jiwa Consumer - Valent Giodinna Lau; Wasiman Wasiman (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aimed to examine the influence of brand image, advertising appeal, and lifestyle on consumer interest in purchasing Janji Jiwa products. A quantitative approach was used in this study. The sampling technique applied was non-probability sampling with a total of 204 respondents. The research data was obtained through the distribution of questionnaires to Janji Jiwa consumers. Data analysis was performed using multiple linear regression with the help of SPSS software version 31. The analysis results indicate that brand image has a t-calculated of 4.266, advertising appeal has a t-calculated of 5.806, and lifestyle has a t-calculated of 5.429, with significance levels of 0.000 for each variable. These findings demonstrate that all three variables have a positive and significant effect on consumer purchase intention. Simultaneously, these three variables explain 71.9% of the influence on consumer purchase interest while the remaining 28.1% is attributable to other factors not examined in this study. These findings underscore the strategic importance of enhancing brand positioning, utilizing persuasive advertising appeals, and aligning marketing initiatives with consumer lifestyles to promote a higher purchase intention.